2015
DOI: 10.1007/s10562-015-1499-2
|View full text |Cite
|
Sign up to set email alerts
|

Methyl Group Modified MCM-41 Supported Schiff-Base Cobalt Complex and Its Catalytic Performance in Cyclohexane Oxidation

Abstract: The mesoporous molecular sieve MCM-41 was amino-functionalized using c-aminopropyltriethoxysilane. The obtained NH 2 -MCM-41 was then hydrophobic modified by methyltriethoxysilane, dimethyldiethoxysilane and trimethylethoxysilane, respectively. N,N 0 -Bis (salicylidene) ethylenediiminocobalt (Cosalen) was grafting into the modified MCM-41 through the complex effect of NH 2 group. The prepared Cosalen/(CH 3 ) n -NH 2 -MCM-41 (n = 0, 1, 2, 3) were characterized by the technique of FT-IR, XRD, N 2 adsorption-deso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Therefore, developing new highly efficient and robust heterogeneous catalysts for industrial-scale selective aerobic oxidation of cyclohexane is of great importance. In the last several years, various heterogeneous catalysts have been widely exploited for cyclohexane catalytic aerobic oxidation. For example, supported metalloporphyrins, transition metals with Schiff base ligands, , cobalt compounds, copper complexes, and metal nanoparticles have been developed to promote the cyclohexane conversion and the selectivity of KA oil under relatively mild and environmentally friendly reaction conditions. However, most of these catalyst systems either required high temperature/pressure or suffered from poor selectivity to KA oil.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, developing new highly efficient and robust heterogeneous catalysts for industrial-scale selective aerobic oxidation of cyclohexane is of great importance. In the last several years, various heterogeneous catalysts have been widely exploited for cyclohexane catalytic aerobic oxidation. For example, supported metalloporphyrins, transition metals with Schiff base ligands, , cobalt compounds, copper complexes, and metal nanoparticles have been developed to promote the cyclohexane conversion and the selectivity of KA oil under relatively mild and environmentally friendly reaction conditions. However, most of these catalyst systems either required high temperature/pressure or suffered from poor selectivity to KA oil.…”
Section: Introductionmentioning
confidence: 99%
“…Most likely some pores were blocked by the aminopropyl and acid ionic liquid. [41] But the average pore diameters decreased in the samples, which suggested that acid ionic liquids and the Cr-salphen/ salten complexes may be well confined in the pores of mesoporous silica.…”
Section: N 2 Sorption Studiesmentioning
confidence: 91%
“…In the XRD pattern ( Figure 3) of pure MCM-41, a very strong reflection at 2θ=1.89° for d100 and also two other weaker reflections at 2θ=3.79° and 4.35° for d110 and d200, respectively, can be indexed to well-ordered mesoporous material of a hexagonal symmetry. [41] After immobilization of Cr complex, the intensity of the peak at (100) decreased largely, the higher angle peaks in the parent sample no longer appeared. It is mainly due to a loss of the mesoporous order.…”
Section: Small Angle X-ray Diffraction Studiesmentioning
confidence: 99%
“…After completion, the amino group functionalized MCM‐41 (M41@N) was separated by centrifugation, washed with ethanol, and dried at 333 K for 8.0 h under reduced pressure (Scheme 1a). [ 23–25 ]…”
Section: Methodsmentioning
confidence: 99%
“…After completion, the amino group functionalized MCM-41 (M41@N) was separated by centrifugation, washed with ethanol, and dried at 333 K for 8.0 h under reduced pressure (Scheme 1a). [23][24][25] The substituted benzaldehydes (12.0 mmol) and M41@N (1.0 g) were added to a bottle containing 40-mL ethanol. The mixture was magnetically stirred at 358 K for 24 h under the atmosphere.…”
Section: General Procedures For the Preparation Of Functionalized Mcm-41mentioning
confidence: 99%